PENGARUH MEDIA PEMBELAJARAN MONOPOLI BAHASA ARAB DALAM PENINGKATKAN PENGUASAAN KOSAKATA BAHASA ARAB SISWA SMP MUHAMMADIYAH 8 TANGGULANGIN - Ramadhani, Ikhuan Farhan; Hikmah, Khizanatul (Jurnal Dedikasi Pendidikan, 2025)
This study aims to determine the effect of the Arabic Monopoly learning media on improving vocabulary (mufrodat) mastery among eighth-grade students at SMP Muhammadiyah 8 Tanggulangin. The background of this research is the students’ low mastery of Arabic vocabulary, which is caused by the lack of innovative and engaging learning media. This study uses a quantitative approach with a One Group Pretest- Posttest Design. The research involved 36 students as subjects. Data collection techniques included observation, interviews, and tests. The results show a significant increase in students’ average scores from 43.11 in the pretest to 91.06 in the posttest. The Paired Sample T-Test yielded a significance value of 0.000 < 0.05, indicating a significant effect of the Arabic Monopoly media on improving students' vocabulary mastery. Therefore, the use of the Monopoly learning media is proven to be effective in enhancing students’ Arabic vocabulary acquisitiona